The Role of Modifying the Core-Vent Implant Thread on Occlusal Load Distribution in Bone (A Finite Element Study) - Abbas Faisal Al-Huwaizi; Salim A Salim
The point of modifying the implant is to produce an optimum stress transmission, hence it seems important to consider every detail of the implant in modification. The study was based on modifying the Core-Vent thread and designing six new threads (55º down, 55º up, 45º down, 45º up, Long down and Long up threads). The results were monitored on specific points market at the cortical bone/implant interface and implant apex. While applying the finite element analysis to the thread designs it was concluded from the results that the 55º down thread showed the best stress distribution.